2021
DOI: 10.3889/oamjms.2021.7074
|View full text |Cite
|
Sign up to set email alerts
|

The Role Vascular Endothelial Growth Factor, Control Glycemic, Lipid Profile, and Hypoxia-inducible Factor 1-Alpha at Type 2 Diabetic Patients in North Sumatera, Indonesia

Abstract: BACKGROUND: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder whose prevalence continues to increase worldwide. Chronic hyperglycemia increases the area of hypoxia that can be measured by markers of hypoxia-inducible factor 1-alpha (HIF-1α) and endothelial cell damage by vascular endothelial growth factor (VEGF) secretion and the association of the course of diabetes mellitus, dyslipidemia is also a risk factor that can aggravate the condition. diabetes mellitus. AIM: The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This finding is in concordance with the study reported by Zhang et al, which reported that VEGF correlated with fasting blood glucose (r=0.483, p<0.001) and HbA1c (r=0.531, p<0.001) levels in healthy people and Type 2 DM subjects. [14], while another study reported the opposite, which finding no significant correlation between HbA1c and FPG with VEGF (p>0.05) [15]. Chronic increases in blood glucose levels in diabetes mellitus subjects can trigger an increase in VEGF production through various pathways.…”
Section: Discussionmentioning
confidence: 95%
“…This finding is in concordance with the study reported by Zhang et al, which reported that VEGF correlated with fasting blood glucose (r=0.483, p<0.001) and HbA1c (r=0.531, p<0.001) levels in healthy people and Type 2 DM subjects. [14], while another study reported the opposite, which finding no significant correlation between HbA1c and FPG with VEGF (p>0.05) [15]. Chronic increases in blood glucose levels in diabetes mellitus subjects can trigger an increase in VEGF production through various pathways.…”
Section: Discussionmentioning
confidence: 95%